A road less travelled: Undergraduate midwifery students' experiences of a decentralised clinical training platform - Olivia B. Baloyi; Gugu G. Mchunu; Charlene Williams; Mary-Ann Jarvis (AOSIS, 2020)
Background: In South Africa, the critical skill base shortage of healthcare workers, the underperforming global health indicators and the planned roll out of the National Health Insurance have burdened South African higher education authorities to rapidly expand nursing student enrolments. The expansion in student numbers has placed increased demands on overstretched educational institutions, and students are confronted with challenges of congestion in classrooms and clinical facilities, while lecturers encounter difficulties in the process of clinical allocation. A solution is to utilise decentralised clinical training platforms (DCTPs) and allocate students in rural hospitals. Aim: To explore and describe undergraduate midwifery students' reflections of their DCTP experiences, in order to inform future practice of decentralisation in student training. Setting: The study was conducted in the nursing discipline of an urban-based university in KwaZulu-Natal, South Africa, involving undergraduate midwifery students. The university had commenced a programme of allocating students to decentralised clinical sites. Method: Elo and Kyngäs' content analysis was used to analyse the experiences of DCTP by undergraduate midwifery students (n = 14) as expressed in a focus group (n = 11) and three individual interviews (n = 3). Results: The following four categories emerged: Recognition as a team member, engaging support, win-win platform and juxtaposed challenges. Conclusion: In the presence of support and teamwork, rural settings can develop undergraduate student midwives, not only in the areas of midwifery competency but also in their personal capacity, and strengthen the responsiveness, preparedness and relevance of midwifery graduates.